IEEE International Geoscience and Remote Sensing Symposium
DOI: 10.1109/igarss.2002.1024996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of digitized Canadian ice charts and passive microwave sea-ice concentrations

Abstract: This paper presents results comparing digitized seaice charts with passive microwave estimates of sea-ice concentration using the NASA Team algorithm. The Canadian ice chart series contains detailed information on sea-ice type during the sea ice growth, consolidation and melt stages for four main ice-covered regions of Canada: the Canadian East Coast, Hudson Bay, East Canadian Arctic and the West Canadian Arctic.Comparison with passive microwave sea-ice concentration estimates over the 1979 to 1996 period show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In addition, at the ice margins and areas of ice breakup, the many different concentrations that can exist within one pixel will be smoothed to an average figure. Several studies have shown that because of the surface melt, in particular, the passive microwave-derived data tend to systematically underestimate ice concentration (e.g., Agnew and Howell, 2003;Shokr and Markus, 2006). When compared to sea-ice charts, the passive microwave sea-ice concentrations derived from the nASA Team algorithm were found to underestimate concentration during summer melt by 20.4% to 33.5%.…”
Section: Background: Measuring Sea-ice Breakupmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, at the ice margins and areas of ice breakup, the many different concentrations that can exist within one pixel will be smoothed to an average figure. Several studies have shown that because of the surface melt, in particular, the passive microwave-derived data tend to systematically underestimate ice concentration (e.g., Agnew and Howell, 2003;Shokr and Markus, 2006). When compared to sea-ice charts, the passive microwave sea-ice concentrations derived from the nASA Team algorithm were found to underestimate concentration during summer melt by 20.4% to 33.5%.…”
Section: Background: Measuring Sea-ice Breakupmentioning
confidence: 98%
“…There is some evidence that CIS charts are more accurate than passive microwave data for estimates of ice concentration, particularly in the presence of surface melt (documentation from Fetterer et al, 2008;Agnew and Howell, 2002). The CIS state that they rarely use passive microwave data for their charts.…”
Section: Canadian Ice Service Chartsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies (e.g., Partington et al, 2003;Agnew and Howell, 2002) have shown that passive microwavederived sea ice data tend to underestimate ice concentration when compared with operational analyses. The Climate Data Record of Passive Microwave Sea Ice Concentration is a blend of output from two algorithms that results in higher ice concentrations overall for a better match with the operational analyses that predate the satellite record.…”
Section: Metrics Of Sea Ice Coveragementioning
confidence: 99%
“…Many algorithms have been developed to retrieve sea ice concentration (SIC) from passive microwave remote sensing data [7]. A large number of studies compared microwave satellite data with other types of satellite information of higher resolution (visible, infrared, and radar) [9][10][11], as well as sea ice charts on their basis [12][13][14]. SIC data obtained using different algorithms were repeatedly compared with each other to reveal their functionality under different ice and weather conditions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%